FEED INFORMATION SYSTEMS AND EXPENDITURE ON PT. SAKURA INDAH PHOTO - Setianto Setianto; M. Taufik A. SKom (Jurnal Sistem Informasi, 1996)
Income and expenditure information system of goods at PT. Sakura's Beautiful photo of this, looks very easy and communicative for users live to see steps that will be done through a menu of revenue and expenditures are made in such a way with a fairly complete description. Views in this program are also made with colors that are not good enough in the sense that saturate the user.